Fabrication of a microcantilever-based aerosol detector with integrated electrostatic on-chip ultrafine particle separation and collection. (7th November 2019) - Bertke, Maik; Xu, Jiushuai; Setiono, Andi; Kirsch, Ina; Uhde, Erik; Peiner, Erwin
Abstract: In this paper, fabrication and testing of a miniaturized microcantilever-based particulate matter detector with integrated electrostatic on-chip ultrafine particle (UFP) separation and collection are presented. Mass added to the sensor causes a resonance frequency shift. To attract naturally charged particles, the cantilever is equipped with a collection electrode. In addition, a µ -channel is integrated, to improve the particle collection efficiency and to enable a size/mass-related particle separation. For electrical read-out, piezo-resistive struts are attached to the cantilever sidewalls near its clamping. This design offers high miniaturization potential, since no integration of transducing electronics on the cantilever beam is needed. The sensors are fabricated using Si bulk material and standard micromachining technology; the cantilevers have a thickness of 3  ±  0.5 µ m, a width of 3.1  ±  0.3 µ m, 5.9  ±  0.4 µ m or 10.5  ±  0.4 µ m and a length of 118.7  ±  0.8 µ m, 168.8  ±  0.8 µ m or 171.2  ±  1 µ m, respectively. To this end, a front-side release process using cryogenic inductive-coupled plasma reactive ion etching was developed, which does not require additional sidewall passivation steps. Testing of the resonator function by operating the sensor inside a scanning electron microscope and reference measurements inside a temperature-controlled test chamber using synthetic carbon UFPs (~160 nm average mass concentration distribution) and a fast mobility particle sizer as a reference instrument were carried out. Here, the ability to detect low UFP mass concentrations in the range  <10 µ g m −3 could be shown with a limit of detection of ~1 µ g m −3 and a collection time of ~10 min. In addition, a voltage dependence of the collection efficiency was found at constant UFP-concentration conditions, which is an indication of size-selective UFP collection.